High order DPA with profiling - Zhen WU; Yi WANG; Guanhao ZHOU (Tongxin xuebao, 2018)
In side channel attack,the masking implementation is one of the most popular counter measures again first order DPA.Presently,high order DPA and high order template attack are often used to attack against masking counter measures.High order DPA,however,targets joint leakage of multiple types of information and therefore needs cross combination of powers at corresponding positions,which is the root of the inefficiency of high order DPA.High order template attack,on the other hand,has to know the random mask in each encrypting at its learning phase,which is rarely satisfied for most adversaries.Be aware of these shortcomings and limitations,the algorithm of high order DPA with profiling used neural network to establish the model of fitting the combination of un-masked intermediate values.Attacking was based on the correlation coefficient between the fitted combination intermediate value and the guessing combination intermediate value.This method eliminated the requirement of knowing the masks at the learning phase of template attack and the requirement of cross combination of powers for high order DPA,and therefore lowered the requirement of learning as well as improved attacking efficiency.Experiments have confirmed the feasibility of this algorithm,as well as its efficiency.